2019
DOI: 10.1038/s41598-018-38058-5
|View full text |Cite
|
Sign up to set email alerts
|

Control of heart rate through guided high-rate breathing

Abstract: Understanding the complex dynamics of cardio-respiratory coupling sheds light on the underlying mechanisms governing the communication between these two physiological systems. Previous research has predominantly considered the coupling at respiratory rates slower than the heart rate and shown that respiratory oscillations lead to modulation and/or synchronization of the heart rate. Whereas the mechanisms of cardio-respiratory communication are still under discussion, peripheral nervous regulation is considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 22 publications
6
40
0
1
Order By: Relevance
“…Although the mechanisms of cardiorespiratory communication have not been fully investigated, prior studies have suggested a possible relationship between the respiratory rate and heart rate. One study detected cardiopulmonary 1:1 entrainment at elevated respiratory rates . Such findings are highly suggestive of direct neural communication between the heart rate and respiratory rate.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the mechanisms of cardiorespiratory communication have not been fully investigated, prior studies have suggested a possible relationship between the respiratory rate and heart rate. One study detected cardiopulmonary 1:1 entrainment at elevated respiratory rates . Such findings are highly suggestive of direct neural communication between the heart rate and respiratory rate.…”
Section: Discussionmentioning
confidence: 96%
“…One study detected cardiopulmonary 1:1 entrainment at elevated respiratory rates. 17 Such findings are highly suggestive of direct neural communication Although respiratory rate has been traditionally used as a vital sign, respiratory rate assessments are known to be a widely neglected entity. [18][19][20][21] Consequently, there is no global agreement on the normal range of respiratory rates for the older adult population.…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by the conclusions of Pokrovskii's work [10,13,14], breathing will be guided at rates close to and exceeding RHR. A detailed description of these experiments and the results with corresponding statistical analysis are published in [15]. This article is looking to analyse the differences in length of synchronization for volunteers of different fitness capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…This can be used to capture intervals of synchronization from a pair of oscillators, also giving access to their phase shift. Cardio-respiratory synchronization is not generally recorded in rest or sleep, it has been observed during specific breathing and/or vocal exercises [99,100].…”
Section: Discussionmentioning
confidence: 99%